KAJIAN GAME ONLINE TERHADAP ANAK DI BAWAH UMUR DI KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO (STUDI KASUS PADA ANAK DI BAWAH UMUR 12 TAHUN) - Sihaloho, Mega Sriulina; Suwu, Evie A. A.; Mumu, Rudy (HOLISTIK, Journal Of Social and Culture, 2020)
The development of science and technology is now increasingly fast and broadly produce products that provide convenience for humans, both in terms of science, education, and entertainment. At present many things are accessed even about children and also through various internet and social media. Internet technology provides a large and varied influence on human life, one of the most popular is in terms of entertainment. Like games in online games that discuss traditional games in ancient times, these online games are widely used by children because these various online games are much more fun, fun and easier to play.This study uses qualitative research taken from the book Sugiyono 2015. From the results of the study found positive and negative consequences of playing online games on minors, but more people feel the negative effects of playing online games.Â Keywords: Online Game Studies; Minors